Just exhaustification. A ‘two stage’ theory of exclusives - Panizza, Daniele; Chierchia, Gennaro (Proceedings of the Amsterdam Colloquium, 2019)
We propose a novel unified semantics for only/just, which addresses the following problems: the problem of only taking scope over a disjunction (cf. [6]), the problem of rank order readings ([8], [4]) and the problem of what only presupposes (cf. [9], [1]). Our proposal is based on the following assumptions: a) only and just are subject to a non vacuity presupposition, b) they only ‘see’ entailment-based alternatives, c) they employ Innocent Exclusion [6], and d) they are not presuppositional but they have however a factive implicature, as proposed by Romoli [12] for soft triggers, i.e. they exhaustify in two stages.